INTEGRASI NILAI-NILAI FILSAFAT PENDIDIKAN ISLAM DALAM MANAJEMEN KURIKULUM DI SEKOLAH-SEKOLAH ISLAM - Setiabudi, Dede Indra; Ari Ramadhana; Galih Permana; Adang Hambali; Hasan Basri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the implementation of the Islamic philosophy of education approach in curriculum management in Islamic schools through library research. The Islamic philosophy of education approach, which emphasizes the integration of spiritual, moral, and intellectual values, is considered to provide a strong foundation for the development of holistic and sustainable curriculum. The research method used is library research by examining relevant literature, including books, journal articles, and educational policy documents. The findings of the research indicate that the Islamic philosophy of education plays a crucial role in shaping curriculum management that can integrate general knowledge with religious values. This approach involves various aspects, including curriculum planning, implementation, and evaluation based on Islamic principles. The literature review reveals that many Islamic schools still face challenges in effectively implementing this approach, especially due to educational dualism and a lack of competent human resources. Literature analysis also shows that factors such as the commitment of school leadership, teacher training, and educational policy support are crucial for the successful implementation of the Islamic philosophy of education approach. This research concludes that the Islamic philosophy of education approach can be an effective paradigm in curriculum management for Islamic schools, focusing not only on academic achievement but also on the character development of students. The study recommends enhancing managerial and pedagogical capacities through professional training and development for educators, as well as developing policies that support the integration of Islamic values into the curriculum. It is hoped that the findings of this research will contribute to efforts to improve the quality of Islamic education in the modern era. Keywords: Islamic philosophy of education, curriculum management, Islamic schools;